Molecular Dynamics at the Immunological Synapse - Pedro Roda-Navarro (Frontiers Research Topics, 2017)
The immunological synapse (IS) is a specialised cell-cell adhesion that mediates antigen acquisition and regulates the activation of lymphocytes. Initial studies of the IS showed a structure composed of stable supra-molecular activation clusters (SMAC) organised during the interaction of helper T lymphocytes with B lymphocytes, working as antigen presenting cells. A central SMAC of coalesced T cell receptors (TCRs) and a peripheral SMAC for cell-cell adhesion were observed. IS with similar structure was later described during antigen acquisition by B cells and during the interaction of NK cells with target and healthy cells. More recent research developed with microscopy systems that improve the spatial and temporal resolution has showed the complex molecular dynamics at the IS that governs lymphocyte activation. Currently, the IS is seen as a three-dimensional structure where signalling networks for lymphocyte activation and endosomal and cytoskeleton machinery are polarised. A view has emerged in which dynamic microclusters of signalling complexes are composed of molecular components attached to the plasma membrane and other components conveyed on sub-synaptic vesicles transported to the membrane by cytoskeletal fibers and motor proteins. Much information is nonetheless missing about how the dynamics of the endosomal compartment, the cytoskeleton, and signalling complexes are reciprocally regulated to achieve the function of lymphocytes. Experimental evidence also suggests that the environment surrounding lymphocytes exposed to different antigenic challenge regulates IS assembly and functional output, making an even more complex scenario still far from being completely understood. Also, although some signalling molecular components for lymphocyte activation have been identified and thoroughly studied, the function of other molecules has not been yet uncovered or deeply characterised. This research topic aims to provide the reader with the latest information about the molecular dynamics governing lymphocyte activation. These molecular dynamics dictate cell decisions. Thus, we expect that understanding them will provide new avenues for cell manipulation in therapies to treat different immune-related pathologies.